2013
DOI: 10.7861/clinmedicine.13-3-278
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic diabetes: old and new approaches to diagnosis

Abstract: -Up to 5% of young adults diagnosed with diabetes have a monogenic aetiology, the most common of which is maturity-onset diabetes of the young (MODY). A definitive molecular diagnosis is important, as this affects treatment, prognosis and family screening. Currently, however, rates of diagnosis are low due to a combination of lack of awareness of the benefits of making the diagnosis and the challenges of differentiating patients with MODY from those with common forms of diabetes. This article aims to introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
25
0
2
Order By: Relevance
“…These studies showed that hsCRP levels are significantly reduced in HNF1A-MODY cases, which is consistent with the fact that the CRP gene is under the regulation of HNF1A, and that HNF1A-MODY cases could be discriminated from other types of diabetes [60][61][62]. In fact, levels of hsCRP discriminated HNF1A-MODY from T2D with high sensitivity and specificity as studies have shown that 70-80% of HNF1A-MODY patients have <0.5 mg/l hsCRP, whilst that was the case in only <20% of type 2 diabetics [60,61,64]. GWAS efforts revealed that HNF1A also plays a role in posttranslational glycoprotein modifications, in particular via upregulating fucosylation of the antennary sections of these proteins [59].…”
Section: How Biomarkers Help To Find and Classify Modysupporting
confidence: 65%
“…These studies showed that hsCRP levels are significantly reduced in HNF1A-MODY cases, which is consistent with the fact that the CRP gene is under the regulation of HNF1A, and that HNF1A-MODY cases could be discriminated from other types of diabetes [60][61][62]. In fact, levels of hsCRP discriminated HNF1A-MODY from T2D with high sensitivity and specificity as studies have shown that 70-80% of HNF1A-MODY patients have <0.5 mg/l hsCRP, whilst that was the case in only <20% of type 2 diabetics [60,61,64]. GWAS efforts revealed that HNF1A also plays a role in posttranslational glycoprotein modifications, in particular via upregulating fucosylation of the antennary sections of these proteins [59].…”
Section: How Biomarkers Help To Find and Classify Modysupporting
confidence: 65%
“…18 This is particularly important in the context of monogenic diabetes because there is the potential to spare a patient from the burden of a lifetime of insulin therapy and the ability to use molecular diagnostic techniques to help screen at-risk family members. Currently, there are ongoing studies looking at the use of highly sensitive C-reactive protein as a biomarker for monogenic diabetes 19 and the excellent MODY risk calculator on the University of Exeter website (www.diabetesgenes.org). 20 ■…”
Section: Discussionmentioning
confidence: 99%
“…Maturity onset diabetes of the young (MODY) is a heterogeneous group of monogenic causes of β-cell dysfunction1 and can account for 1–5% of all diabetes cases diagnosed before the age of 45 years 2. Hepatocyte nuclear factor 1A MODY (HNF1A-MODY) is the most common form of MODY in adults, accounting for about 50% cases in the UK 1.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte nuclear factor 1A MODY (HNF1A-MODY) is the most common form of MODY in adults, accounting for about 50% cases in the UK 1. Individuals are normoglycaemic in childhood and diabetes typically presents in the second to fourth decade of life 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation